2016
DOI: 10.1186/s12879-016-1467-5
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B in Ghana: a systematic review & meta-analysis of prevalence studies (1995-2015)

Abstract: BackgroundAlthough, chronic hepatitis B (HBV) is considered to be of significant public health importance in Ghana, not many reviews detailing the burden (prevalence) of the disease have been conducted. This study was aimed at summarizing the available information and to make an accurate estimate of HBV infection prevalence in Ghana over the last two decades (1995–2015).MethodsA systematic search was conducted in PubMed, ScienceDirect, Google Scholar and Africa Journals Online (AJOL) databases to retrieve prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
173
9
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(207 citation statements)
references
References 52 publications
23
173
9
2
Order By: Relevance
“…and 12.3%; 95% CI 11.3-13.4%32 ) and a study among recent (< 5 years) migrants of Ghanaian ethnicity in Spain (15/92; 16.3%; 95% CI 9.8-24.8%) 33. …”
mentioning
confidence: 95%
“…and 12.3%; 95% CI 11.3-13.4%32 ) and a study among recent (< 5 years) migrants of Ghanaian ethnicity in Spain (15/92; 16.3%; 95% CI 9.8-24.8%) 33. …”
mentioning
confidence: 95%
“…The main factors associated with MTCT were investigated quantitatively, while the responses from the questionnaires were used to evaluate how HBsAg positive pregnancies were managed in the clinic. Given that the estimated national prevalence of individuals with CHB is approximately 12.3% in Ghana [10], the finding that only three of the 51 infants were HBsAg positive in this study was somewhat lower than anticipated. This is an important observation and appears to align more closely with the 8.3% HBV maternofetal transmission rate in chronic carriersobserved by Candotti et al in Kumasi [22] and the 8.7% seroprevalence reported by Amidu et al in the nearby Ashanti region [23].…”
Section: Discussionmentioning
confidence: 57%
“…In Ghana, chronic infection with HBV is considered highly endemic. In a recent systematic review of 30 studies across all 10 regions, Ofori-Asenso & Agyeman found that hepatitis B surface antigen (HBsAg) seropositivity was 12.3% [10]. These figures are more or less in line with a systematic review conducted by Schweitzer et al which estimated that the prevalence of chronic HBV in Ghana was 12.9% [11].…”
Section: Introductionmentioning
confidence: 66%
“…However, a lower prevalence estimate (2.03%) was obtained from the Eastern Mediterranean countries [101]. The current prevalence among blood donors was much lower than findings from Nigeria 14%, Ghana 11.75%, Burkina Faso 11.73%, and Cameroon 10.5% [96][97][98][99]. The possible explanation could be due to high endemicity of the virus in the said countries than Ethiopia.…”
Section: Discussionmentioning
confidence: 95%